A unique Pd-catalysed Heck arylation as a remote trigger for cyclopropane selective ring-opening - Singh, Sukhdev; Bruffaerts, Jeffrey; Vasseur, Alexandre; Marek, Ilan (Nature communications, 2017)
Combining functionalization at a distant position from a reactive site with the creation of several consecutive stereogenic centres, including the formation of a quaternary carbon stereocentre, in acyclic system represents a pinnacle in organic synthesis. Here we report the regioselective Heck arylation of terminal olefins as a distant trigger for the ring-opening of cyclopropanes. This Pd-catalysed unfolding of the strained cycle, driving force of the chain-walking process, remarkably proved its efficiency and versatility, as the reaction proceeded regardless of the molecular distance between the initiation (double bond) and termination (alcohol) sites. Moreover, employing stereodefined polysubstituted cyclopropane vaults allowed to access sophisticated stereoenriched acyclic scaffolds in good yields. Conceptually, we demonstrated that merging catalytically a chain walking process with a selective C–C bond cleavage represents a powerful approach to construct linear skeleton possessing two stereogenic centres. Functionalizing multiple, distant sites across a molecule is a challenge. Here the authors report a remote functionalization strategy, whereby an initial Heck reaction leads to chain-walking of palladium across a molecule, ring-opening cyclopropanes while retaining the stereochemistry in the product.